Exploring Rhetorical Approaches in Indonesian Master Thesis Introductions - Wakerkwa, Dian Agustina Purwanto (Journal of English Education Program, 2025)
A thesis is a compulsory assignment that should be created at the end of the study by the master"™s students to earn their degree. The Introduction is one of the most challenging sections of this thesis. Therefore, this study aimed to analyze the rhetorical moves organization used by Indonesian master"™s students in their theses introductions, using Swales"™ move analysis CARS model (1990). The selected theses were within the scope of improving the students' writing skills. The findings demonstrated that the writers' most common strategy in writing the Introduction section was to define their research area, indicating their attempt to create a convincing argument for the originality of their work. The findings offer pedagogical implications for lecturers in developing academic writing teaching materials and for students composing their thesis introductions.